Short-Sale Strategies and Return Predictability - Diether, Karl B.; Lee, Kuan-Hui; Werner, Ingrid M. (Review of Financial Studies, 2009)
[We examine short selling in US stocks based on new SEC-mandated data for 2005. There is a tremendous amount of short selling in our sample: short sales represent 24% of NYSE and 31% of Nasdaq share volume. Short sellers increase their trading following positive returns and they correctly predict future negative abnormal returns. These patterns are robust to controlling for voluntary liquidity provision and for opportunistic risk-bearing by short sellers. The results are consistent with short sellers trading on short-term overreaction of stock prices. A trading strategy based on daily short-selling activity generates significant positive returns during the sample period.]